MENA Quarterly Economic Brief January 2016 The Economic Effects of War and Peace - Devarajan, Shantayanan (Middle East and North Africa Economic Monitor, 2016)
The July 2015 nuclear deal between Iran and Permanent Members of the UN Security Council and Germany (P5+1), with the attendant lifting of sanctions on Iran, will have significant consequences for the global, regional and national economies. First, Iran's return to the oil market, coupled with increased production from Libya (should the conflict subside) will keep world oil prices low. Secondly, once sanctions and restrictions on financial transactions are relaxed, Iran's trade, which had both declined in absolute terms and shifted away from Europe towards Asia and the Middle East, is likely to pick up. Thirdly, the Iranian economy, which has been in recession for the past two years, will receive a major boost from increased oil revenues--conservatively estimated at about